Microstructural characterization of oxide dispersion strengthened (ODS) Fe-12Cr-0.5Y2O3 alloy - Shamsudin F.M.; Radiman S.; Abdullah Y.; Hamid N.A. (American Institute of Physics Inc., 2023)
Oxide dispersion strengthened (ODS) ferritic alloy containing 12wt% Cr and 0.5wt% Y2O3 was prepared by mechanical alloying (MA) method and then compacted into bulk shape. Field emission scanning electron microscopy (FESEM) was performed to characterize the microstructure of milled alloy powder. The fragments and nanoclusters of Y2O3 were observed in this alloy powder. FESEM-EDS mapping on the milled alloy powder reveal the uniformity of the element distribution achieved by the alloy. The Y element is finely dispersed into the alloy matrix and the O element is observed indicating the presence of oxides throughout the alloy sample. The compacted alloy was then heat treated at 1050C and analyzed by field emission scanning electron microscope (FESEM). The formations of nano-scale Y2O3 were observed after the heat treatment process of alloy indicating the dispersion and incorporation of Y2O3 nanoparticles into the alloy matrix. 2016 Author(s).